Mass casualty incidents and healthcare system challenges: Capacity adaptation and emergency medical coordination - Matejić, Tomislav; Kaštelan, Snježana; Lovrić, Ivana; Kaštelan Brumen, Uršula; Đukić, Katarina (Crisis Management Days, 2025)
Mass casualty incidents (MCIs) put enormous pressure on healthcare systems, requiring a fast and well-organized response. These events, such as large-scale accidents, natural disasters, and pandemics, lead to a sudden increase in critically injured patients, demanding quick hospital capacity expansion, effective triage, and coordinated emergency medical services. One of the biggest challenges is ensuring hospitals can accommodate many patients without compromising care quality. This requires opening additional treatment areas, using mobile medical units, and transferring stable patients to other facilities to free up critical care beds. Ensuring a steady supply of essential medical resources, such as ventilators, surgical equipment, and blood products is crucial for effective response. Triage is essential in prioritising care and using resources efficiently. Standardised triage systems, supported by digital tools and artificial intelligence, can help medical teams quickly assess injury severity and decide on the best course of action. Wearable monitoring devices can track patients’ vital signs, allowing for better transport and hospital admission decisionmaking. Effective emergency coordination depends on strong communication between hospitals, emergency responders, and government agencies. Using digital platforms and real-time data sharing ensures faster decision-making and better resource allocation. Helicopter transport and mass evacuation protocols can improve patient distribution, reducing strain on individual facilities. Technology plays a growing role in MCI management. AI-driven systems can predict patient influx and help distribute medical supplies more efficiently. Geographic information systems can map affected areas, guiding emergency teams to where they are most needed. Electronic health records allow quick access to patient information, ensuring seamless care transitions between medical teams. Long-term preparedness is key to strengthening healthcare system resilience. Regular training, simulation drills, and disaster response education for healthcare workers improve response efficiency. International collaboration in emergency planning, shared protocols, and resource exchanges enhance global readiness for future crises. MCIs require a proactive approach integrating medical, technological, and logistical strategies. By improving triage methods, strengthening communication networks, and investing in healthcare infrastructure, medical systems can respond more effectively and save more lives. Future efforts should focus on better preparedness, advanced predictive tools, and stronger international cooperation to minimise the impact of mass casualty events.